2023
DOI: 10.3390/languages8010076
|View full text |Cite
|
Sign up to set email alerts
|

The Dance of Pauses in Poetry Declamation

Abstract: In poetry declamation, the appropriate use of prosody to cause pleasure is essential. Among the prosodic parameters, pause is one of the most effective to engage the listeners and provide them with a pleasant experience. The declamation of three poems in two varieties of Portuguese by ten Brazilian Portuguese (BP) speakers and ten European Portuguese (EP) speakers, balanced for gender, was used as a corpus for evaluating the degree of pleasantness by listeners from the same language variety. The distributions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, our analysis revealed that languages featuring shorter gaps do not necessarily have longer overlaps (Question #4). Interestingly, this trend was reversed in the case of BP, a language distinguished by longer gaps, extended pauses (as also discussed in [16]), and longer instances of overlap. Additionally, our investigation unveiled that the duration of overlaps displays a distinct pattern of language grouping, potentially indicating a divergent pace in the communication process, distinct from the patterns observed in pauses and gaps, and this is seemingly the case of BP, in particular.…”
Section: Discussionmentioning
confidence: 89%
“…However, our analysis revealed that languages featuring shorter gaps do not necessarily have longer overlaps (Question #4). Interestingly, this trend was reversed in the case of BP, a language distinguished by longer gaps, extended pauses (as also discussed in [16]), and longer instances of overlap. Additionally, our investigation unveiled that the duration of overlaps displays a distinct pattern of language grouping, potentially indicating a divergent pace in the communication process, distinct from the patterns observed in pauses and gaps, and this is seemingly the case of BP, in particular.…”
Section: Discussionmentioning
confidence: 89%
“…77-134) and Colonna & Romano (2023). For the Ibero-Romance languages, in particular, see and Barbosa (2022Barbosa ( , 2023. 2 Among the works on the topic of voice in Spanish authors, see Mistrorigo (2018).…”
Section: Introductionmentioning
confidence: 99%